2002
DOI: 10.1590/s0100-29452002000300012
|View full text |Cite
|
Sign up to set email alerts
|

Fitorreguladores no aumento da frutificação efetiva e partenocarpia em peras cv. Garber

Abstract: RESUMO -O trabalho foi realizado em pereiras da cultivar Garber (Pyrus communis x Pyrus pyrifolia), com o objetivo de verificar o efeito de ácido giberélico (AG 3 ), ácido naftalenoacético (ANA), aminoetoxivinilglisina (AVG) e tidiazurom (TDZ) no aumento da frutificação e na indução e desenvolvimento de frutas partenocárpicas. Durante a plena floração, aplicaram-se sobre os cachos florais 13 diferentes tratamentos: (50; 300 e 500 mg.L ), sendo que, na testemunha, foi aplicada somente água. A polinização entomó… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…O thidiazuron (TDZ) (N-fenil-N-1,2,3-tidiazol-5-tiureia) é uma citocinina sintética, cuja aplicação no florescimento pode proporcionar aumento da frutificação efetiva de macieiras e pereiras (PETRI et al 2001;TAVARES et al 2002). Segundo WERTHEIM & WEBSTER (2005), a aplicação de substâncias como TDZ e GA 3 estimulam a divisão celular e aumento do tamanho das células, promovendo o crescimento dos frutos e minimizando os efeitos do etileno na abscisão destes.…”
Section: Tratamentosunclassified
“…O thidiazuron (TDZ) (N-fenil-N-1,2,3-tidiazol-5-tiureia) é uma citocinina sintética, cuja aplicação no florescimento pode proporcionar aumento da frutificação efetiva de macieiras e pereiras (PETRI et al 2001;TAVARES et al 2002). Segundo WERTHEIM & WEBSTER (2005), a aplicação de substâncias como TDZ e GA 3 estimulam a divisão celular e aumento do tamanho das células, promovendo o crescimento dos frutos e minimizando os efeitos do etileno na abscisão destes.…”
Section: Tratamentosunclassified
“…According to Vieira et al (2016), lighter fruits in apple trees treated with TDZ are correlated with higher fruit production. Tavares et al (2002), reported a higher degree of deformity in fruits produced under TDZ application. These are elongated fruits that do not stand upright on a flat surface, lacking the characteristic apple shape.…”
Section: Resultsmentioning
confidence: 96%
“…Many studies, performed on different plants, suggest various hypotheses for low fruiting. Among them are: a shortage or lack of pollinators (Manente-Balestieri and Machado, 1999;Paiva et al, 1999;Kiill and Drumond, 2001;Tavares et al, 2002;Nogueira and Arruda, 2006;Petri et al, 2008), unavailability of nutrients in the soil (Ferreira et al, 2003), herbivory and predation affecting the production and flower or fruit viability (ManenteBalestieri and Machado, 1999;Vieira and Grabalos, 2003;Nogueira and Arruda, 2006;Carvalho et al, 2007;Aguiar and Gaglianone, 2008), lack of resources available on the plant (Manente-Balestieri and Machado, 1999;Vieira and Grabalos, 2003;Nogueira and Arruda, 2006;Carvalho et al, 2007;Aguiar and Gaglianone, 2008), selfpollination, since the species are normally cross-pollinated (Nogueira and Arruda, 2006) and abiotic factors such as temperature, humidity and precipitation (Ferreira et al, 2003;Nogueira and Arruda, 2006;Pereira and Mayer, 2008). Soil characteristics such as pH, aeration, temperature and nutrient availability may also directly affect the plants reproductive success by influencing the production and viability of the fruits (Ferreira et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Kiill and Drummond (2001) in their study of Gliricidia sepium, Tavares et al (2002) with pears and Paiva et al (1999) with acerolas). This failure is probably due to the shortage or deficiency of pollinators (Manente-Balestieri and Machado, 1999;Nogueira and Arruda, 2006;Petri et al, 2008).…”
Section: Discussionmentioning
confidence: 99%